2013
DOI: 10.1111/dsu.12199
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Eyebrow Hypotrichosis Using Bimatoprost: A Randomized, Double-Blind, Vehicle-Controlled Pilot Study

Abstract: Bimatoprost 0.03% ophthalmic solution applied daily for 9 months improves the appearance of eyebrows noticeably more than vehicle, without side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…9,10 A single-center, randomized, double-masked, vehicle-controlled study evaluated bimatoprost 0.03% with daily application to the eyebrows for 9 months in 20 women with mild to moderate hypotrichosis. 11 The bimatoprost group demonstrated improvement in eyebrow growth at all time points, with maximum changes seen at Month 7. Subject satisfaction at Month 9 with eyebrow fullness/thickness and darkness/color was higher in the bimatoprost group than that in the vehicle group.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…9,10 A single-center, randomized, double-masked, vehicle-controlled study evaluated bimatoprost 0.03% with daily application to the eyebrows for 9 months in 20 women with mild to moderate hypotrichosis. 11 The bimatoprost group demonstrated improvement in eyebrow growth at all time points, with maximum changes seen at Month 7. Subject satisfaction at Month 9 with eyebrow fullness/thickness and darkness/color was higher in the bimatoprost group than that in the vehicle group.…”
Section: Discussionmentioning
confidence: 84%
“…This may be attributed to natural regrowth of the eyebrows because subjects were instructed not to groom their eyebrows in the treatment area. 11 Improvements in the control setting have also been observed with other hair growth products, such as 2% minoxidil. In a randomized, double-masked, split-face study conducted in 39 men and women with eyebrow hypotrichosis receiving minoxidil 2% lotion or placebo, there was a slight increase in eyebrow enhancement in 51% of subjects receiving minoxidil and 23% of subjects receiving placebo.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, adjustment for multiple statistical tests was performed in only 16 (9·9%) manuscripts with ≥ two statistical tests performed. Only one study reported the actual number of statistical tests performed . The most common method of correction was that of Bonferroni (seven studies, 43·8%), followed by Holm–Bonferroni's (three studies, 18·8%) and Dunn's (two studies, 12·5%).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, a synthetic PGA, bimatoprost, besides being used to lower intraocular pressure is also approved only by American Food and Drug Administration, but not by European Union for cosmetic purposes to increase eyelash length, thickness, and darkness in normal patients and in patients with palpebral hypotrichosis [3,6,11]. The effectiveness of bimatoprost for eyelash growth has been demonstrated by clinician ratings, digital image analysis, and patient satisfaction [12][13][14], but the ability of PGAs to increase eyelash growth does not appear limited to bimatoprost. Two other PGAs, latanoprost and travoprost, both used to treat ocular hypertension, have been associated with eyelash changes, including increases in length and darkness ( Figure 1) [15,16].…”
Section: Introductionmentioning
confidence: 99%